2014 IEEE Conference on Evolving and Adaptive Intelligent Systems (EAIS) 2014
DOI: 10.1109/eais.2014.6867482
|View full text |Cite
|
Sign up to set email alerts
|

Symbol recognition with a new autonomously evolving classifier autoclass

Abstract: A new algorithm for symbol recognition is proposed in this paper. It is based on the AutoClass classifier [1], [2], which itself is a version of the evolving fuzzy rule-based classifier eClass [3] in which AnYa[1] type of fuzzy rules and data density are used. In this classifier, symbol recognition task is divided into two stages: feature extraction, and recognition based on feature vector. This approach gives flexibility, allowing us to use various feature sets for one classifier. The feature extraction is pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…As it was stated in the previous work on TEDAClass [ 18], and contrary to the formulations of eClass [ 16] and AulaClass [ 17], we do not define any global statistical characteristics over the data.…”
Section: Ll Teda Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…As it was stated in the previous work on TEDAClass [ 18], and contrary to the formulations of eClass [ 16] and AulaClass [ 17], we do not define any global statistical characteristics over the data.…”
Section: Ll Teda Descriptionmentioning
confidence: 99%
“…Nowadays, a lot of fuzzy systems are serving to solve classification, regression and clustering problems. Recently introduced algorithms include DE C [ 24], AutoClass [ 17], eClass [ 16], FLEXF I SClass [ 25]. Some of these algorithms are included in comparison in the experimental section.…”
Section: Fuzzy Systems Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept was defined in AnYa [1], [3] and was patented in [2]. This concept is also the underlying component of AutoClass and TEDA-Class [4]. All of which come from Angelov's sound work of RDE [3].…”
Section: IImentioning
confidence: 99%
“…It is concluded that random regions should be carefully selected and should be chosen close enough to true operating regions of a system being modelled. The MATLAB codes of pRVFLN is made publicly available in 4) to help further study.…”
mentioning
confidence: 99%